US Counterterrorism and the Human Rights of Foreigners Abroad Putting the Gloves Back On? - Heupel, Monika (Routledge Studies in Human Rights, 2022)
This book examines why the United States has introduced safeguards that are designed to prevent their counterterrorism policies from causing harm to non-US citizens beyond US territory. It investigates what made US policymakers take steps to "put the gloves back on" through five case studies on the emergence of such safeguards related to the right not to be tortured, the right not to be arbitrarily detained, the right to life (in connection with targeted killing operations), the right to seek asylum (in connection with refugee resettlement), and the right to privacy (in connection with foreign mass surveillance). The book exposes two mechanisms - coercion and strategic learning - which explain why the United States has introduced what the authors refer to as "extraterritorial human rights safeguards", thus demonstrating that the emerging norm that states have human rights obligations towards foreigners beyond their borders constrains policy choices. This book will be of key interest to scholars and students of human rights, counterterrorism, US foreign policy, human rights law, and more broadly to political science and international relations.